Avaliação da influência da matéria orgânica, na determinação quantitativa de metais em amostras de sedimento, por espectrometria de absorção atômica e análise de metais traços por fluorescência de raios-X - Martins, Ilton Sávio Batista (2011)
The proposal of this work is to evaluate the influence of the organic matter on the results of the analyses of the metals (Zn, Pb, Al, Cu, Cr, Fe, Cd e Ni) for Atomic Absorption Spectrometry (AAS), so much in the extraction stage as in the reading using for that the chemometrics. They were used for this study sample of bottom sediment collected in river Jundiaí in the vicinity of the city of Macaíba-RN, commercial humus and water of the station of treatment of sewer of UFRN. Through the analyses accomplished by EAA it was verified that the interference of the organic matter happens in the extraction stage and not in the reading. With relationship to the technique of X Ray Fluorescence Spectrometry (XRFS), the present work has as intended to evaluate the viability of this technique for quantitative analysis of trace metals (Cr, Ni, Cu, Zn, Rb, Sr and Pb) in having leached obtained starting from the extraction with acqua regia for an aqueous solution. The used samples constitute the fine fraction (<0.063 mm) of sediments of swamp of the river Jundiaí. The preparation of tablets pressed starting from the dry residue of those leached it allowed your analysis in the solid form. This preliminary study shows that, in the case of the digestion chemistry partially of the fine fractions of bottom sediments used for environmental studies, the technique of applied EFRX to the analysis of dry residues starting from having leached with acqua regia, compared her it analyzes of the leached with ICP-OES, it presents relative mistakes for Cu, Pb, Sr and Zn below 10%